2017
DOI: 10.1080/14728222.2017.1311864
|View full text |Cite
|
Sign up to set email alerts
|

Sodium potassium adenosine triphosphatase (Na/K-ATPase) as a therapeutic target for uremic cardiomyopathy

Abstract: Introduction Clinically, patients with significant reductions in renal function present with cardiovascular dysfunction typically termed, uremic cardiomyopathy. It is a progressive series of cardiac pathophysiological changes, including left ventricular diastolic dysfunction and hypertrophy (LVH) which sometimes progress to left ventricular dilation (LVD) and systolic dysfunction in the setting of chronic kidney disease (CKD). Uremic cardiomyopathy is almost ubiquitous in patients afflicted with end stage rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 148 publications
(164 reference statements)
0
18
0
Order By: Relevance
“…Redox signaling contributes to cardiac hypertrophy and even more important oxidative stress contributes to the transition of adaptive to maladaptive cardiac hypertrophy, named maladaptive remodeling. Oxidative stress can damage cells by growth factor-independent activation of cardiac growth regulation (Calamaras et al, 2015), can inactivate NO leading to loss of myocyte-specific NO function (Rassaf et al, 2006; Lüneburg et al, 2016), can directly reduce cardiomyocyte function by oxidative modification of sarcomere proteins such as tropomyosin (Heusch et al, 2010b; Canton et al, 2011) or sarcoplasmatic reticulum proteins (i.e., SERCA; Qin et al, 2017), can induce a calcium desensitization of myofibrils (Wang et al, 2008), can activate the Na-K-ATPase (Wang et al, 2017a), can damage mitochondrial function (Ide et al, 2001; Sverdlov et al, 2016), or can induce cell death (apoptosis, necrosis; Redza-Dutordoir and Averill-Bates, 2016). Therefore, ROS defense strategies of the cells are necessary for cell survival and functional stabilization in both ventricles.…”
Section: Oxidative Stress In the Heartmentioning
confidence: 99%
“…Redox signaling contributes to cardiac hypertrophy and even more important oxidative stress contributes to the transition of adaptive to maladaptive cardiac hypertrophy, named maladaptive remodeling. Oxidative stress can damage cells by growth factor-independent activation of cardiac growth regulation (Calamaras et al, 2015), can inactivate NO leading to loss of myocyte-specific NO function (Rassaf et al, 2006; Lüneburg et al, 2016), can directly reduce cardiomyocyte function by oxidative modification of sarcomere proteins such as tropomyosin (Heusch et al, 2010b; Canton et al, 2011) or sarcoplasmatic reticulum proteins (i.e., SERCA; Qin et al, 2017), can induce a calcium desensitization of myofibrils (Wang et al, 2008), can activate the Na-K-ATPase (Wang et al, 2017a), can damage mitochondrial function (Ide et al, 2001; Sverdlov et al, 2016), or can induce cell death (apoptosis, necrosis; Redza-Dutordoir and Averill-Bates, 2016). Therefore, ROS defense strategies of the cells are necessary for cell survival and functional stabilization in both ventricles.…”
Section: Oxidative Stress In the Heartmentioning
confidence: 99%
“…Furthermore, the bioreactive substances such as histamine, lipids, and cytokines released by the “passenger” leucocytes that may exert direct effect on metabolic and physical changes associated with the senescence in cells are related to RBC storage medium lesion [3]. Other evidence also suggests that hypothermic storage of red blood cells may lead to reduced metabolism and energy demand, subsequently rendering ATP-dependent sodium potassium pump inoperative and ultimately leading to the free movement of sodium into the cells and potassium out of the cells [4]. Current research indicates that RBC hypothermic storage lesion is responsible for the association of blood transfusion with an increased length of stay in the hospital, increased infections, multiple organ system failure, and ultimately increased morbidity and mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…CKD is a gradually debilitating disorder that has been associated with series of pathophysiological processes, causing an overall dysregulation of kidney function and predisposes to kidney injury [ 1 ]. The CKD afflicted population in US is estimated to be around 14% with highest mortality observed in the patients with stage 5 CKD or end stage renal disease (ESRD) [ 2 ]. The persistence of CKD is often exacerbated by other comorbidities, particularly diabetes, obesity and cardiovascular diseases [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have observed that the adipocytes themselves are an important source of oxidant stress in models of obesity/metabolic syndrome and that mediators directly tied to the cellular phenotype of these adipocytes play a causal role in dysregulation of metabolic homeostasis [ 13 , 14 , 15 ]. Investigators have also demonstrated that the UT indoxyl sulfate (IS) increased ROS production via the NOX pathway specifically in 3T3-L1 adipocytes [ 2 ]. Evidence suggests that alterations in adipose tissue can also exacerbate the inflammatory state of adipocytes.…”
Section: Introductionmentioning
confidence: 99%